Dioxin-like compounds formation mediated by Fe3+-montmorillonite: The substituent effects of halophenols. (August 2022) - Wang, Yi; Peng, Anping; Ding, Keqiang; Ren, Lingxiao; Chen, Zeyou; Gu, Cheng
Abstract: Toxic dioxin or/and dioxin-like compounds could be naturally formed from the reaction of halophenols on Fe 3+ -montmorillonite minerals under ambient conditions. Given that the toxicities and productions of dioxin or/and dioxin-like compounds are largely determined by the number, species, and position of the carried halogen atoms, it is necessary to explore the substituent effects on the reaction of halophenols with Fe 3+ -montmorillonite. Herein, Fe 3+ -montmorillonite catalyzed polymerizations of six halophenols were examined in a wide range of relative humidity (10%∼80%) using combinations of mass spectrometry identifications and density functional theory calculations. Results show that both the position and species of the substituents substantially impact the reaction rate, product species, and transformation pathways. In general, regardless of humidity ortho -substituted chlorophenols are more reactive than meta -substituted chlorophenols, which is also supported by the density functional theory calculations indicating that the ortho positions are more likely to be attacked. Regarding substituent species, bromophenols are slightly more reactive and also more easily affected by humidities than chlorophenols, which is due to the weaker electron absorbing ability of the bromine atom than the chlorine atom. Hydroxylated polyhalogenated diphenyl ethers are more frequently detected polymerization products, although hydroxylated polyhalogenated biphenyls are greater quantity of products. Overall, this study provides useful information for understanding the natural formation of dioxin or/and dioxin-like compounds mediated by clay minerals and underlying reaction mechanisms. Graphical abstract: Image 1 Highlights: The heterogeneous polymerization is highly depended to the substituents position. Ortho positions of the phenolic hydroxyl group are more likely to be attacked. Bromophenols are slightly more reactive than chlorophenols. HO-PXDEs are more frequently detected and HO-PXBs are of higher response. The reaction with 2, 4, 5-TCP could form 2, 3, 7, 8-TCDD precursor.